Proceedings of the 2016 International Conference on Electrical, Mechanical and Industrial Engineering 2016
DOI: 10.2991/icemie-16.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Analysis of Diethyl Ether Blends in Gasoline Engine Operated with Ethanol

Abstract: Abstract-This paper investigates the effect of using unleaded gasoline with di ethyl ether blends on spark ignition engine (SI engine) performance, exhaust and combustion analysis. A four stroke, single cylinder SI engine was used for conducting this study. Exhaust emissions were analysed for carbon monoxide (CO), Hydrocarbon (HC), and Oxides of nitrogen (NOx) and carbon dioxide (CO 2 ) using unleaded gasoline, ethanol and di ethyl ether blends with different percentages of fuel at varying engine torque condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It is observed that 6% DEE blend shows decrease in HC emission at maximum load. It could be because of the addition of DEE reduced the ignition delay [12] and enhanced the combustion characteristics. Figure 3(b) shows the variations of HC emissions at inlet air temperature of 22°C with the load.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that 6% DEE blend shows decrease in HC emission at maximum load. It could be because of the addition of DEE reduced the ignition delay [12] and enhanced the combustion characteristics. Figure 3(b) shows the variations of HC emissions at inlet air temperature of 22°C with the load.…”
Section: Resultsmentioning
confidence: 99%
“…There is a decrease in energy content of the blended fuel and increase in fuel consumption depending on the amount and type of oxygenates added to the gasoline. This resulted in change of the air to fuel ratio and ensures complete combustion of fuel into CO2 and H2O [12,13]. Ethanol addition to unleaded gasoline increase the engine torque, power and fuel consumption and reduce CO, NOx and HC emissions.…”
Section: Introductionmentioning
confidence: 99%
“…So, this situation caused to obtain lower indicated thermal efficiency (ITE) on HCCI combustion. Balaji et al, [14] found BTE by about 15%, 14.5% and 14.8 % with 10% ethanol-2.5% DEE, 10% ethanol-5% DEE and 10% ethanol-7.5% DEE test fuels respectively for the 50% engine load in a SI engine. It was found that the increase of DEE additive decreased effective efficiency for 25, 50 and 75% engine loads in a direct injection diesel engine [7].…”
Section: Fig 4 the Influences Of Dee On Sfc Versus Engine Speedmentioning
confidence: 97%
“…But, SFC increased with DEE10. Balaji et al, [14] concluded that fuel consumption increased with the increase of DEE addition at the same engine torque in a spark ignition engine. Kumar et al, [15] found that BSFC increased by 16% and 8.5% with 6% and 3% DEE fuel mixtures respectively at maximum engine load and 22°C inlet air temperature in a SI engine.…”
Section: Fig 4 the Influences Of Dee On Sfc Versus Engine Speedmentioning
confidence: 99%
See 1 more Smart Citation